Socio-economic status and constraints faced by dairy farmers of Kangra District, Himachal Pradesh - Shubham; Sharma, Ravinder; sharma, Subhash; Bishist, Rohit; Shilpa (Indian Journal of Dairy Science, 2024)
Dairy farming is an imperative part of the rural economy in hilly areas. It helps in improving the socio-economic status of the farmers, provides nutrition and employment opportunities to the population. Milk production of Himachal Pradesh is low (1.531MT) and contributes only 0.7% to total milk production of India. Kangra district of Himachal Pradesh is second largest producer of milk in the state, therefore present study was undertaken to study the socio-economic status and constraints in dairy farming in the district. A comprehensive questionnaire was prepared to analyse the socio-economic status, cropping patterns, milk productivity and constraints in dairy farming. Analysis was done by Garret ranking technique. In most of the farmers were of small category and were rearing the animals for subsistence purpose. The large farmers of the study area were adopting dairy as a profession. High cost of construction of animal shed, lack of availability of green fodder, heat detection problem, low prices of dairy products and lack of emergency veterinary services are the major constraints faced by the farmers in the study area. In order to sustain and improve milk production, the focus need to be done on green fodder cultivation, milk marketing channels, low cost housing designs, improving AI coverage and establishing mobile veterinary clinics for attracting rural youth to adopt dairy as a profession.